Pengaruh Pengembangan Karir dan Work Life Balance terhadap Kinerja Karyawan pada PT Agung Toyota Kota Jambi - AS, Sakinah; Azima, Khuluqon; Syukri, Muhammad (Universitas Batanghari Jambi, 2025)
This research aims to analyze the influence of career development and work-life balance on the performance of PT Agung Toyota Jambi City employees. The type of research used is quantitative research with an associative approach. The research population included all employees of PT Agung Toyota Jambi City, namely 80 people, with a sampling technique using the saturated sample method. Data analysis was carried out using multiple linear regression. The research results show that simultaneously and partially there is a positive and significant influence between the variables of career development and work-life balance on the performance of PT Agung Toyota Jambi City employees.